Readiness of girls aged 10-12 years for an early menarche: a transtheoretical model of behavioural change analysis - Ni Made Diaris; Rina Listyowati; Pande Putu Januraga (Universitas Udayana, 2017)
Background and purpose: Studies have revealed that girls are now having menarche much younger. An early menarche put young girls at higher risk for physical and psychological problems. This study aims to explore stages of readiness of girls aged 10-12 years for an early menarche. Method: A qualitative study was conducted in Denpasar City. A total of 20 students both from primary school and junior high school aged between 10 and 12 years were purposively selected to participate in the study. Ten students had menarche while the other 10 were yet to have menarche. Data were collected through in-depth interviews at the schools after approval from parents was obtained. Data were analysed using a thematic approach. Results: All informants have conceded the pre-contemplation and contemplation stages. Most of them were at the preparation stage. Some children were at the action stage though some were just entered the action stage. In-depth interviews revealed that the majority of informants understood the basic knowledge of menstruation. Their mother provided information and supports after they had menarche. However, some informants stated that they were panic, ashamed, and anxious during their menarche. They also believed that several activities including washing hair, drinking icy beverages, and eating sweets were forbidden. Conclusion: Some girls are not fully at the action stage leading to fear and shame when they had menarche. This suggests that a more comprehensive education program and psychological supports especially from mother should target younger girls to prepare them for an early menarche.